2015
DOI: 10.1007/s10803-015-2629-9
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Burden of Care in Mothers of Children with Autism Spectrum Disorder or Intellectual Disability

Abstract: Compared to other mothers, mothers of children with autism spectrum disorder (ASD) or intellectual disability (ID) have higher rates of treatment episodes for psychiatric disorders. We aimed to estimate the maternal burden of care by comparing the length of hospitalisations for psychiatric disorders and the treatment rates for psychiatric disorders after the birth in mothers of children with ASD/ID and no psychiatric history to that of other mothers with no psychiatric history. Mothers of children with ID of k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…2015; Fairthorne et al . 2016). Publication bias was not assessed as there were inadequate numbers of included studies to properly assess a funnel plot or conduct more advanced regression‐based assessments.…”
Section: Resultsmentioning
confidence: 99%
“…2015; Fairthorne et al . 2016). Publication bias was not assessed as there were inadequate numbers of included studies to properly assess a funnel plot or conduct more advanced regression‐based assessments.…”
Section: Resultsmentioning
confidence: 99%
“…It has long been known that parenting a child with a developmental disability presents multiple challenges to the family across the lifespan. The very fact of the child's disability would be distressing to any parent, and early 1 3 even evidence of more treatment episodes and longer hospitalizations for psychiatric disorders in mothers of these children, despite no previous psychiatric history (Fairthorne et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have found a positive association between caregiving and healthcare use (primary, secondary, emergency and psychological service visits and medication use). This increased use has been attributed to caregiver psychological distress, high child healthcare use, child behavioural problems, and the specific diagnoses of ASD and learning disability (Thurston et al 2011;Brehaut et al 2019;Le et al 2016;Fairthorne et al 2016).…”
Section: Discussionmentioning
confidence: 99%